The Clean Hotel Room: A Public Health Imperative. (March 2020) - Sembajwe, Grace; Spaeth, Kenneth; Dropkin, Jonathan
As the hotel industry leads in environmental, social, and corporate governance (ESG) criteria, cleaning hotel rooms on a daily basis promotes public health. This activity leads to cleaner air and reduces the potential for exposure and spread of biohazards. Daily room cleaning is also in direct concordance with building a robust and effective green (environmental) policy. Although guests will always have the option to choose individual frequency, at the hotel management and policy level, daily room cleaning and checks are part of a sound greening program, consistent with advancements and innovation in environmental and social governance programs that are integral to public safety and health.